High thermal conductivity and breakdown voltage resistant circuit board material, circuit board and preparation method thereof

Through magnetic orientation and bidirectional freezing technology, three-dimensional porous structure filler is formed and combined with epoxy-benzoxazine composite resin, the thermal conductivity and breakdown voltage resistance of existing high-thermal conductivity materials during high breakdown voltage and long-term high-voltage operation are solved. The problem of inability to take into account can achieve the effect of efficient thermal conductivity and high breakdown voltage resistance, while reducing production costs.

CN118909508BActive Publication Date: 2025-02-25JINAN JUNHAN ELECTRONIC MATERIALS CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410950194.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2023-11-28
Filing Date
2024-07-16
Publication Date
2025-02-25
Estimated Expiration
2044-07-16

AI Technical Summary

Technical Problem

When existing high thermal conductivity materials are in operation with high breakdown voltage and long-term high voltage, the thermal conductivity and breakdown voltage resistance cannot be taken into account, and the production cost is relatively high.

Method used

By magnetically oriented and bidirectional freezing of spherical alumina, α-ferrous tetraoxide and graphene, a three-dimensional porous structure filler is formed, and it is immersed in an epoxy-benzoxazine composite resin to form a composite heat conduction Insulation layer.

Benefits of technology

The specific properties of high thermal conductivity and high breakdown voltage are achieved, reducing production costs, while improving the mechanical and thermal conductivity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118909508B_ABST
    Figure CN118909508B_ABST
Patent Text Reader

Abstract

This invention relates to high thermal conductivity and high breakdown voltage resistant circuit board materials, circuit boards, and their preparation methods. A three-dimensional porous filler is obtained by magnetically oriented and bidirectionally frozen a dispersion suspension of spherical alumina, α-ferric oxide, and graphene. This three-dimensional porous filler is then thoroughly impregnated in a mixture of epoxy-benzoxazine composite resin and a curing agent under vacuum, and coated onto a substrate circuit board. The coated layer is then cured at high temperature to form a composite thermally conductive and insulating layer, i.e., the high thermal conductivity and high breakdown voltage resistant circuit board material. The high thermal conductivity and high breakdown voltage resistant circuit board material is prepared on the substrate layer, and then a conductive circuit layer is deposited on the composite thermally conductive and insulating layer using a PVD coating process with a target material to obtain the high thermal conductivity and high breakdown voltage resistant circuit board. This invention fully optimizes and screens novel inorganic-organic combined thermally conductive and insulating composite materials to achieve the specific properties of high thermal conductivity and high breakdown voltage, exhibiting excellent performance, a relatively simple process, and low cost.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a high-heat-conductivity and high-breakdown-voltage circuit board material, a circuit board and a preparation method thereof, and belongs to the technical field of insulating materials and composite electronic materials. Background Art

[0002] New energy vehicles are developing in full swing, with obvious advantages in power performance, intelligence, cost saving, etc., especially high-voltage-driven new energy vehicles that can be quickly charged are the general trend of the market. Not only the efficiency is improved, the heat loss is reduced, and the power can also be increased. Because of the technological progress of "electronic and electrical components", the demand for high breakdown voltage and high thermal conductivity materials is imminent. According to the CEI60664 standard, if the working voltage is 500V, the interlayer breakdown voltage needs to be as high as 8KV to 10KV DC, which is converted into the insulation thickness of the "metal substrate", then it must be at least 150um or more. The thickness of the conductive substrate is proportional to the thermal resistance. The thickness of more than 150um has a great negative effect on the thermal conductivity. Therefore, the metal substrate that can withstand the high voltage demand of new energy vehicles cannot have both voltage resistance and high thermal conductivity. The development of materials with better breakdown voltage capability (1.3KV / mil) than most thermal conductive substrates, which can withstand long-term high voltage work during the life cycle and have certain thermal conductivity characteristics (at least 2W ISO ASTMD5470) has become a potential key demand in the market. One of the ideas is to reduce the thickness without affecting the reliability of the breakdown voltage.

[0003] The common existing technology is to use an aluminum substrate as the metal base layer, and form a three-layer single-sided board by constructing a circuit layer and an insulation layer. Among them, the insulation layer is the core technology of the aluminum substrate, which mainly plays the functions of bonding, insulation and heat conduction. The aluminum substrate insulation layer is the largest thermal barrier in the power module structure. The better the thermal conductivity of the insulation layer, the more conducive it is to the diffusion of heat generated during the operation of the device, and the more conducive it is to reducing the operating temperature of the device. However, at present, the thermal conductivity of the insulation layer of the aluminum substrate commonly used on the market is 3W-5W, which has poor thermal conductivity, and has defects such as low breakdown voltage, low peel strength, and uneven thickness of the conductive line.

[0004] There are many insulating layer materials available at present, such as polymer materials. The most effective way to improve the thermal conductivity of polymer materials is to add an appropriate amount of high thermal conductivity fillers to the polymer matrix. For thermal conductive materials that mainly play an insulating role, thermal conductive fillers generally select metal oxides (BeO, MgO, Al:Os, NiO, etc.), carbides (SiC, BC, etc.) and metal nitrides (A1N, SigN, BN, etc.). Filled thermally conductive insulating polymer materials are ordinary insulating polymer materials with thermally conductive fillers added. Through the interaction between the thermally conductive fillers, a mesh-like or chain-like thermal conductive network is formed in the polymer matrix, thereby improving the thermal conductivity. However, since the powders with good thermal conductivity in the thermal conductive fillers, such as AlN and BN, are expensive, the production cost of downstream industries is increased.

[0005] Epoxy resin composite materials have been widely used in the field of circuit boards due to their good adhesion, corrosion resistance and electrical insulation. However, the thermal conductivity of pure epoxy resin is 0.15-0.21 W / mk, and it usually needs to be filled and modified to improve its thermal conductivity. The thermal conductivity of graphene is as high as 5×10 3 W / mK, high thermal stability. With the maturity of graphene production technology in recent years, graphene / epoxy resin composite materials will be widely used in the field of circuit board heat dissipation. However, the current method is to simply use graphene sheets as fillers and composite them with epoxy resin to form a one-dimensional composite material, and its performance has not achieved a qualitative breakthrough.

[0006] The most common method to improve the thermal conductivity of resin-based materials is the filling method. However, a higher filling amount is required to obtain a higher thermal conductivity. However, a high filling amount will increase the viscosity of the material during mixing and processing, which will bring difficulties to processing, increase the density of the composite material, and damage the mechanical properties of the composite material. Therefore, constructing a well-oriented three-dimensional filling interconnected network is one of the most effective methods to achieve high thermal conductivity. The methods for constructing a three-dimensional network structure thermal conductive composite material mainly include freeze-drying orientation method, electrophoretic deposition method, electrostatic flocking method, air-laid-needle felt method and 3D printing method. These methods can significantly improve the thermal conductivity of the composite material while ensuring a low filler content.

[0007] The freeze-drying orientation method is a method of controlling the vertical temperature gradient so that the ice grows vertically upward, thereby arranging the filler vertically along the direction of the ice and maintaining the vertical direction under the action of the adhesive. Through freeze-drying orientation, the filler can form an oriented structure with parallel arrangement, and heat can be quickly transferred in the oriented structure, so that a higher thermal conductivity can be obtained. The freeze-drying orientation method is divided into unidirectional and bidirectional freezing methods according to the freezing direction. The bidirectional freezing method is to place a wedge-shaped polydimethylsiloxane (PDMS) base on a traditional orientation freezing platform, and utilize the different temperature gradients at different heights of the wedge-shaped platform, as well as the temperature and speed differences of the flowing slurry when moving on the sloped cold platform. By introducing a low thermal conductivity PDMS wedge structure between the solution and the frozen surface, temperature gradients in both the horizontal and vertical directions are constructed at the same time, thereby constructing a long-range ordered orientation structure (see the attached figure for the principle). Figure 1 ). The bidirectional freezing method enables the controllable preparation of complex multi-scale structures of materials, and this three-dimensional structure will have more excellent mechanical properties. Summary of the invention

[0008] The purpose of the present invention is to overcome the above-mentioned shortcomings and provide a high thermal conductivity and breakdown voltage resistant circuit board material and a preparation method thereof. The material achieves the specific properties of high thermal conductivity and high breakdown through a prefabricated three-dimensional structure and an inorganic-organic combination.

[0009] The technical solution adopted by the present invention is:

[0010] A high thermal conductivity and breakdown voltage resistant circuit board material is obtained by magnetically orienting a dispersed suspension of spherical alumina, α-ferroferric oxide and graphene and performing bidirectional freezing to obtain a three-dimensional porous structure filler. The three-dimensional porous structure filler is immersed in a mixture of epoxy-benzoxazine composite resin and curing agent under vacuum and thoroughly infiltrated, then coated on a substrate circuit board, and the temperature of the infiltrated coating layer is adjusted to cure at high temperature to obtain a composite thermal conductive insulation layer.

[0011] The weight ratio of the spherical alumina to α-ferroferric oxide to graphene is in the range of 3:1:5;

[0012] The weight ratio of epoxy resin to benzoxazine resin in the epoxy-benzoxazine composite resin is 3 to 5:1;

[0013] The mass ratio of the three-dimensional porous structure filler to the epoxy-benzoxazine composite resin is in the range of 1:8-10.

[0014] The method for preparing the above-mentioned high thermal conductivity and breakdown voltage resistant circuit board material comprises the following steps:

[0015] (1) Spherical alumina, α-ferroferric oxide and graphene are added to water, and ultrasonic dispersion and mixing are performed under an external magnetic field to obtain a uniform dispersed suspension, and the dispersed suspension is magnetically oriented under the action of the external magnetic field; the mass ratio of graphene to spherical alumina and α-ferroferric oxide is 5:3:1;

[0016] (2) placing the magnetically oriented dispersion into a PDMS wedge-shaped structure mold, using low-temperature ethanol as a freezing source to cool to -50 to -60°C, and freezing ice crystals along the horizontal and vertical temperature gradients. After the dispersion is completely frozen, the mold is moved to a freeze dryer for freeze drying to obtain a three-dimensional porous structure filler;

[0017] (3) adding epoxy resin to an organic mixed solvent and stirring evenly, and adding benzoxazine resin in a weight ratio of 3 to 5:1 of epoxy resin to benzoxazine resin, stirring and mixing to obtain an epoxy-benzoxazine composite resin;

[0018] (4) adding a curing agent to the epoxy-benzoxazine composite resin at a mass ratio of 15 to 25:1 of the epoxy-benzoxazine composite resin to the curing agent, and stirring the mixture evenly;

[0019] (5) Immersing the obtained three-dimensional porous structure filler into the mixture of epoxy-benzoxazine composite resin and curing agent obtained in step (4) under vacuum, and coating it on the substrate after it is completely infiltrated; the mass ratio of the three-dimensional porous structure filler to the epoxy-benzoxazine composite resin is in the range of 1:8 to 10;

[0020] (6) The temperature of the coated layer after being wetted is adjusted to perform high-temperature curing and molding to obtain a composite thermally conductive insulating layer.

[0021] The particle size of the spherical alumina in step (1) of the above preparation method is 10 to 200 nm.

[0022] The ultrasonic dispersion in step (1) is performed for 20-30 min, and the fixed magnetic field strength ranges from 0.2 to 1 T, preferably 300 mT.

[0023] The freeze dryer described in step (2) is controlled at a temperature of -60°C and a pressure of 0.05-0.1 Pa, and freeze drying is performed for 48 hours.

[0024] The organic mixed solvent described in step (3) is a mixture of acetonitrile, toluene and dichloromethane. The organic mixed solvent is added according to a weight ratio of epoxy resin to organic mixed solvent of 1:3-4. The molecular weight of the epoxy resin ranges from 500 to 2500. The viscosity of the obtained epoxy-benzoxazine composite resin is 100-200cp at 25°C.

[0025] The curing agent described in step (4) is imidazole, succinic acid, sebacic acid, triethylamine, pyridine or pyrrole.

[0026] The high temperature curing described in step (6) is to pre-cure at 120-145°C for 2-3 hours and then cure at 150-175°C for 10-14 hours.

[0027] Another object of the present invention is to provide a high thermal conductivity and breakdown voltage resistant circuit board and a preparation method thereof.

[0028] The high thermal conductivity and breakdown voltage resistant circuit board comprises, in sequence, a composite thermal conductive insulating layer on the lower surface of a substrate layer, a substrate layer, a composite thermal conductive insulating layer on the upper surface of the substrate layer, and a conductive circuit layer; the composite thermal conductive insulating layer adopts the high thermal conductivity and breakdown voltage resistant circuit board material prepared above.

[0029] The substrate layer is made by mixing one or more of copper, copper alloy, aluminum, aluminum alloy, magnesium, magnesium alloy, iron, and iron alloy.

[0030] The conductive circuit layer is made of one or more materials including copper, copper alloy, aluminum, aluminum alloy and silver.

[0031] The thickness of the substrate layer is 0.1-0.5 mm, the thickness of the composite heat-conducting insulation layer is 10-35 μm, and the thickness of the conductive circuit layer is 15-35 μm.

[0032] The method for preparing a high thermal conductivity and breakdown voltage resistant circuit board includes the steps of preparing a high thermal conductivity and breakdown voltage resistant circuit board material on a substrate layer according to the above method, and also includes the step of depositing a conductive circuit layer on the composite thermal conductive insulating layer using a target material through a PVD (physical vapor deposition) coating process.

[0033] The beneficial effects of the present invention are:

[0034] The present invention adopts electromagnetic field induced orientation of ferrosoferric oxide and aluminum oxide, prefabricated three-dimensional structure of graphene as substrate, utilizes the polycyclic and phenolic hydroxyl structure unique to benzoxazine to make it structurally cross-linked with epoxy groups to form epoxy-benzoxazine composite resin, and utilizes layer assembly and bidirectional freezing technology to construct a composite thermal conductive insulation layer material with a highly thermally conductive and highly ordered 3D thermal conductive network.

[0035] The use of prefabricated three-dimensional structures can more easily build an effective heat conduction path in the composite material, because the contact thermal resistance between the nanofillers is much lower than the contact thermal resistance between the fillers and the polymer matrix. At the same time, the two-dimensional layer structure gives it a large specific surface area, making it easier to overlap together to form a heat conduction network with good heat transfer performance when constructing a three-dimensional network structure. Heat can be quickly transferred along the network, thereby achieving efficient heat dissipation. Moreover, the thermal conductivity of the composite material is not only related to the structure of the matrix itself, but also to the content, particle size and morphology of the filler, performance and interface performance between each other. The present invention also fully optimizes and screens a new type of thermal conductive insulation composite material of inorganic-organic combination to achieve the specific performance of high thermal conductivity and high breakdown. Compared with existing high thermal conductivity insulation materials and circuit boards, it has excellent performance, simpler process and lower cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 A schematic diagram of the prior art bidirectional freezing method for preparing three-dimensional graphene materials; (bidirectional means forming temperature gradients in both horizontal and vertical directions under a wedge-shaped PDMS structure mold);

[0037] Figure 2 It is a schematic diagram of a bidirectional freezing reaction device;

[0038] Figure 3 The electron microscope images of the samples before and after bidirectional freezing of the present invention; a is the particle state of filler before bidirectional freezing, and b is the state of lamellar after freezing;

[0039] Figure 4 This is a schematic diagram of the structure of the high thermal conductivity and breakdown voltage resistant circuit board of the present invention, 1. substrate layer, 2. composite thermal conductive insulation layer, 3. conductive circuit layer. DETAILED DESCRIPTION

[0040] The present invention is further described below with reference to specific embodiments.

[0041] In the present invention, the base material of the three-dimensional porous structure material is mainly a composite epoxy resin, and the filling material is a carbon composite material with graphene as an important component. Therefore, the two-way freezing freeze-drying orientation method is selected to efficiently realize the three-dimensional structure of the filling material. The specific operation equipment is as follows Figure 2 .

[0042] Preparation and molding of PDMS wedge-shaped structure: A square copper sheet (4 cm side length, 1 mm thickness) was used, and a PTFE square tube (10 mm side length, 20 mm height, 2 mm thickness) was glued to the copper sheet as a reaction container. It was placed on an inclined platform with a certain slope, and polydimethylsiloxane (PDMS) solution was poured in until the entire copper surface was just covered. The temperature was raised to 80°C and cured for two hours to obtain a PDMS wedge-shaped structure.

[0043] Embodiment 1 A method for preparing a circuit board material with high thermal conductivity and breakdown voltage resistance comprises the following steps:

[0044] (1) A 3 mg / mL graphene dispersion, a 6 mg / mL spherical alumina dispersion, and a 0.5 mg / mL α-ferroferric oxide dispersion were mixed in a mass ratio of 5:3:1 between graphene, spherical alumina, and α-ferroferric oxide, and then ultrasonically dispersed for 30 minutes to obtain a uniform dispersed suspension, and then the dispersed suspension was placed in a fixed magnetic field of 300 mT to complete magnetic orientation molding;

[0045] (2) placing the magnetically oriented dispersed suspension into the above-mentioned PDMS wedge-shaped structure mold and using low-temperature ethanol as a freezing source to cool to -50 to -60°C, ice crystals are bidirectionally frozen along the horizontal and vertical temperature gradients. After the dispersed liquid is completely frozen, the mold is moved to a freeze dryer, the temperature is controlled at -60°C, the pressure is 0.05 to 0.1 Pa, and freeze-dried for 48 hours to obtain a three-dimensional porous structure filler;

[0046] (3) adding an epoxy resin (molecular weight 2500) to an organic mixed solvent in a mass ratio of 1:3, wherein the organic mixed solvent is a mixed solvent of acetonitrile, toluene and dichloromethane, stirring at room temperature for 1 hour, and then adding benzoxazine resin in a mass ratio of 4:1 of epoxy resin to benzoxazine resin, stirring for 2 hours, and measuring its viscosity to be 150cp at 25°C, thereby obtaining an epoxy-benzoxazine composite resin;

[0047] (4) adding imidazole curing agent in a mass ratio of epoxy-benzoxazine composite resin to curing agent of 20:1 and mixing evenly;

[0048] (5) immersing the obtained three-dimensional porous structure filler into a uniformly mixed mixture of epoxy-benzoxazine composite resin and curing agent, wherein the mass ratio of the three-dimensional porous structure filler to the epoxy-benzoxazine composite resin is 1:8, degassing under vacuum at room temperature for 1 h, and coating the filler on a substrate 0.1 mm copper foil using a coating machine, with a coating thickness of 35 μm;

[0049] (6) The sample was placed at 135° C. for pre-curing for 2 h, and then cured at 150° C. for 10 h to perform curing molding of the product to obtain the final product.

[0050] Embodiment 2 High thermal conductivity and breakdown voltage resistant circuit board and preparation method thereof:

[0051] A high thermal conductivity and breakdown voltage resistant circuit board comprises, in sequence, a composite thermal conductive insulating layer on the lower surface of a substrate layer, a substrate layer, a composite thermal conductive insulating layer on the upper surface of the substrate layer, and a conductive circuit layer; the substrate layer and the composite thermal conductive insulating layer are made of the high thermal conductivity and breakdown voltage resistant circuit board material on a copper foil substrate prepared in the above embodiment 1, and then the composite thermal conductive insulating layer is subjected to sputtering ion plating using a copper target, and the film thickness is controlled to be 15 μm, to obtain a high thermal conductivity and breakdown voltage resistant circuit board.

[0052] Embodiment 3 A method for preparing a circuit board material with high thermal conductivity and breakdown voltage resistance comprises the following steps:

[0053] (1) A graphene dispersion with a concentration of 2 mg / mL, a spherical alumina dispersion with a concentration of 5 mg / mL, and an α-ferroferric oxide dispersion with a concentration of 0.4 mg / mL were mixed in a mass ratio of graphene to spherical alumina to α-ferroferric oxide of 5:3:1, and then ultrasonically dispersed for 30 minutes to obtain a uniform dispersed suspension, and then the dispersed suspension was placed in a fixed magnetic field of 300 mT to complete magnetic orientation molding;

[0054] (2) placing the magnetically oriented dispersed suspension into the above-mentioned PDMS wedge-shaped structure mold, using low-temperature ethanol as a freezing source to cool to -50 to -60°C, and freezing ice crystals along the horizontal and vertical temperature gradients. After the dispersed liquid is completely frozen, the mold is moved to a freeze dryer, the temperature is controlled at -60°C, the pressure is 0.05 to 0.1 Pa, and freeze-dried for 48 hours to obtain a three-dimensional porous structure filler;

[0055] (3) adding an epoxy resin (molecular weight 1500) to an organic mixed solvent at a mass ratio of 1:4, wherein the organic mixed solvent is a mixed solvent of acetonitrile, toluene and dichloromethane, stirring at room temperature for 1 hour, and then adding benzoxazine resin at a mass ratio of 3:1 of epoxy resin to benzoxazine resin, continuing stirring for 2 hours, and measuring its viscosity at 200cp at 25°C to obtain an epoxy-benzoxazine composite resin;

[0056] (4) adding adipic acid curing agent in a mass ratio of epoxy-benzoxazine composite resin to curing agent of 20:1 and mixing evenly;

[0057] (5) immersing the obtained three-dimensional porous structure filler into a uniformly mixed mixture of epoxy-benzoxazine composite resin and curing agent, wherein the mass ratio of the three-dimensional porous structure filler to the epoxy-benzoxazine composite resin is 1:8, degassing under vacuum at room temperature for 1 h, and coating the filler on a substrate of 0.1 mm aluminum foil using a coating machine, with a coating thickness of 35 um;

[0058] (6) The sample prepared in (5) was placed at 130°C for pre-curing for 2 hours, and then cured at 165°C for 12 hours. The product was cured and formed to obtain the final product.

[0059] Embodiment 4 High thermal conductivity and breakdown voltage resistant circuit board and preparation method thereof:

[0060] A high thermal conductivity and breakdown voltage resistant circuit board comprises, in sequence, a composite thermal conductive insulating layer on the lower surface of a substrate layer, a substrate layer, a composite thermal conductive insulating layer on the upper surface of the substrate layer, and a conductive circuit layer; the substrate layer and the composite thermal conductive insulating layer are made of the high thermal conductivity and breakdown voltage resistant circuit board material on an aluminum foil substrate prepared in the above-mentioned embodiment 3, and then the composite thermal conductive insulating layer is subjected to sputtering ion plating using a copper target, and the film thickness is controlled to be 20 μm, to obtain a high thermal conductivity and breakdown voltage resistant circuit board.

[0061] Embodiment 5 A method for preparing a circuit board material with high thermal conductivity and breakdown voltage resistance comprises the following steps:

[0062] (1) A graphene dispersion with a concentration of 5 mg / mL, a spherical alumina dispersion with a concentration of 8 mg / mL, and an α-ferroferric oxide dispersion with a concentration of 0.6 mg / mL were mixed in a mass ratio of graphene to spherical alumina to α-ferroferric oxide of 5:3:1, and then ultrasonically dispersed for 30 minutes to obtain a uniform dispersed suspension, and then the dispersed suspension was placed in a fixed magnetic field of 300 mT to complete magnetic orientation molding;

[0063] (2) placing the magnetically oriented dispersed suspension into the above-mentioned PDMS wedge-shaped structure mold, using low-temperature ethanol as a freezing source to cool to -50 to -60°C, and freezing ice crystals along the horizontal and vertical temperature gradients. After the dispersed liquid is completely frozen, the mold is moved to a freeze dryer, the temperature is controlled at -60°C, the pressure is 0.05 to 0.1 Pa, and freeze-dried for 48 hours to obtain a three-dimensional porous structure filler;

[0064] (3) adding an epoxy resin (molecular weight 2000) to an organic mixed solvent in a mass ratio of 1:3, wherein the organic mixed solvent is a mixed solvent of acetonitrile, toluene and dichloromethane, stirring at room temperature for 1 hour, and then adding benzoxazine resin in a mass ratio of 4:1 of epoxy resin to benzoxazine resin, continuing to stir for 2 hours, measuring its viscosity to be 200cp at 25°C, and obtaining an epoxy-benzoxazine composite resin;

[0065] (4) adding pyridine curing agent in a mass ratio of epoxy-benzoxazine composite resin to curing agent of 20:1, and stirring and mixing evenly;

[0066] (5) immersing the obtained three-dimensional porous structure filler into a uniformly mixed mixture of epoxy-benzoxazine composite resin and curing agent, wherein the mass ratio of the three-dimensional porous structure filler to the epoxy-benzoxazine composite resin is 1:10, degassing under vacuum at room temperature for 1 h, and coating the filler on a substrate of 0.1 mm aluminum foil using a coating machine, with a coating thickness of 35 um;

[0067] (6) The sample was placed at 130°C for pre-curing for 2 hours, and then cured at 165°C for 12 hours. The product was cured and formed to obtain the final product.

[0068] Example 6 High thermal conductivity and breakdown voltage resistant circuit board and preparation method thereof:

[0069] A high thermal conductivity and breakdown voltage resistant circuit board comprises, in sequence, a composite thermal conductive insulating layer on the lower surface of a substrate layer, a substrate layer, a composite thermal conductive insulating layer on the upper surface of the substrate layer, and a conductive circuit layer; the substrate layer and the composite thermal conductive insulating layer are made of the high thermal conductivity and breakdown voltage resistant circuit board material on an aluminum foil substrate prepared in the above-mentioned embodiment 5, and then the composite thermal conductive insulating layer is subjected to sputtering ion plating using a copper target, and the film thickness is controlled to be 18 μm, thereby obtaining a high thermal conductivity and breakdown voltage resistant circuit board.

[0070] Comparative Example 1: Take a certain amount of epoxy resin (molecular weight 1500) 80g, add 4g of mixed curing agent composed of adipic acid and imidazole solid, and vacuum degas for 1h at 60℃. Use a coating machine to coat on the substrate 0.1mm copper foil, and the coating thickness is 35um. Place the sample at 130℃, pre-cure for 2h, and then cure at 165℃ for 12h to obtain a copper foil sample. Then use a copper target to use sputtering ion plating on the resin layer, and the film thickness is controlled to be 10um to obtain a voltage circuit board.

[0071] Comparative Example 2: (a circuit board using epoxy resin, modified by adding fillers, but without compounding benzoxazine resin)

[0072] (1) 2 mg / mL of graphene dispersion, 5 mg / mL of spherical alumina dispersion and 0.4 mg / mL of α-ferroferric oxide were mixed in a mass ratio of graphene to spherical alumina to α-ferroferric oxide of 5:3:1, and then ultrasonically dispersed for 30 minutes to obtain a uniform mixed dispersion. The above-mentioned composite was then placed in a fixed magnetic field of 300 mT to complete magnetic orientation molding.

[0073] (2) placing the magnetically oriented dispersed suspension into a PDMS wedge-shaped structure mold, using low-temperature ethanol as a freezing source to cool to -50 to -60°C, and ice crystals along the inclined surface of the wedge structure to form two horizontal and vertical temperature gradients for bidirectional freezing. After the dispersed liquid is completely frozen, the mold is moved to a freeze dryer, the temperature is controlled at -60°C, the pressure is 0.05 to 0.1 Pa, and freeze-dried for 48 hours to obtain a three-dimensional porous structure filler;

[0074] (3) adding epoxy resin (molecular weight 2000) into an organic mixed solvent in a mass ratio of 1:3, wherein the organic mixed solvent is a mixed solvent of acetonitrile, toluene and dichloromethane, and stirring at room temperature for 1 h;

[0075] (4) Add pyridine curing agent in a mass ratio of epoxy resin to curing agent of 15:1, and stir to mix evenly;

[0076] (5) immersing the obtained three-dimensional porous structure filler into a uniformly mixed mixture of epoxy resin and curing agent, wherein the mass ratio of the three-dimensional porous structure filler to the epoxy resin is 1:6, degassing under vacuum at room temperature for 1 h, and coating the filler on a substrate of 0.1 mm aluminum foil using a coating machine, with a coating thickness of 35 μm;

[0077] (6) The sample is placed at 120°C for pre-curing for 2 hours, and then cured at 150°C for 10 hours. The product is cured and formed to obtain the final product.

[0078] Comparative Example 3 High thermal conductivity and breakdown voltage resistant circuit board and preparation method thereof:

[0079] A high thermal conductivity and breakdown voltage resistant circuit board comprises, in sequence, a composite thermal conductive insulating layer on the lower surface of a substrate layer, a substrate layer, a composite thermal conductive insulating layer on the upper surface of the substrate layer, and a conductive circuit layer; the substrate layer and the composite thermal conductive insulating layer are made of the high thermal conductivity and breakdown voltage resistant circuit board material on an aluminum foil substrate prepared in the above-mentioned comparative example 2, and then the composite thermal conductive insulating layer is subjected to sputtering ion plating using a copper target, and the film thickness is controlled to be 18 μm, thereby obtaining a high thermal conductivity and breakdown voltage resistant circuit board.

[0080] Thermal conductivity test of materials:

[0081] The thermal diffusion coefficients of graphene / epoxy-benzoxazine composites at different graphene loadings were determined by transient laser flash point method, following the test standards of ASTM E-1461, DIN EN 821 and DIN 30905. The thermal diffusion coefficient α is obtained by formula (1).

[0082]

[0083] In formula (1), d is the thickness of the sample (mm), and the thermal conductivity λ (W / (m·K)) can be obtained from the thermal diffusion coefficient α (mm 2 / s), specific heat C (p J / (g·K)) and density ρ (g / cm 3 ) is obtained by multiplying them, as shown in formula (2).

[0084] λ = α × Cp × ρ (2).

[0085] The comparison of product test performance results of different embodiments is shown in Table 1:

[0086] Table 1 Performance parameters of different products

[0087]

Claims

1. High thermal conductivity and breakdown voltage resistant circuit board material, characterized by: The invention is a composite thermal insulation layer obtained by magnetically orienting a dispersed suspension of spherical aluminum oxide, α-ferroferric oxide and graphene and performing bidirectional freezing. The three-dimensional porous structure filler is immersed in a mixture of epoxy-benzoxazine composite resin and curing agent under vacuum and thoroughly infiltrated, and then coated on a substrate circuit board. The temperature of the infiltrated coating layer is adjusted and high-temperature cured to obtain the composite thermal insulation layer. The weight ratio of the spherical aluminum oxide, α-ferroferric oxide and graphene is in the range of 3:1:5; the weight ratio of epoxy resin to benzoxazine resin in the epoxy-benzoxazine composite resin is in the range of 3-5:1; and the mass ratio of the three-dimensional porous structure filler to the epoxy-benzoxazine composite resin is in the range of 1:8-10.

2. The method for preparing the high thermal conductivity and breakdown voltage resistant circuit board material according to claim 1, characterized in that: The steps include: (1) Spherical alumina, α-ferroferric oxide and graphene are added to water, and ultrasonic dispersion and mixing are performed under an external magnetic field to obtain a uniform dispersed suspension, and the dispersed suspension is magnetically oriented under the action of the external magnetic field; the mass ratio of graphene to spherical alumina and α-ferroferric oxide is 5:3:1; (2) The magnetically oriented dispersion is placed in a PDMS wedge-shaped structure mold, and low-temperature ethanol is used as a freezing source to cool the temperature to -50~-60°C. Ice crystals are bidirectionally frozen along the horizontal and vertical temperature gradients. After the dispersion is completely frozen, the mold is moved to a freeze dryer for freeze drying to obtain a three-dimensional porous structure filler. (3) adding epoxy resin to an organic mixed solvent and stirring evenly, and adding benzoxazine resin in a weight ratio of 3 to 5:1 of epoxy resin to benzoxazine resin, stirring and mixing to obtain an epoxy-benzoxazine composite resin; (4) adding a curing agent to the epoxy-benzoxazine composite resin in a mass ratio of 15 to 25:1 of the epoxy-benzoxazine composite resin to the curing agent, and stirring the mixture evenly; (5) Immersing the obtained three-dimensional porous structure filler into the mixture of epoxy-benzoxazine composite resin and curing agent obtained in step (4) under vacuum, and coating it on the substrate after it is completely infiltrated; the mass ratio of the three-dimensional porous structure filler to the epoxy-benzoxazine composite resin is in the range of 1:8-10; (6) The temperature of the coated layer after infiltration is adjusted to perform high-temperature curing and molding to obtain a composite thermal conductive insulation layer.

3. The method for preparing a circuit board material with high thermal conductivity and breakdown voltage resistance according to claim 2, characterized in that: The freeze dryer described in step (2) is controlled at a temperature of -60°C and a pressure of 0.05-0.1 Pa, and freeze drying is performed for 48 hours.

4. The method for preparing a circuit board material with high thermal conductivity and breakdown voltage resistance according to claim 2, characterized in that: The organic mixed solvent in step (3) is a mixture of acetonitrile, toluene and dichloromethane. The organic mixed solvent is added in a weight ratio of epoxy resin to organic mixed solvent of 1:3-4. The molecular weight of the epoxy resin ranges from 500 to 2500. The viscosity of the obtained epoxy-benzoxazine composite resin is 100-200cp at 25°C.

5. The method for preparing a circuit board material with high thermal conductivity and breakdown voltage resistance according to claim 2, characterized in that: The curing agent described in step (4) is imidazole, succinic acid, sebacic acid, triethylamine, pyridine or pyrrole.

6. The method for preparing a circuit board material with high thermal conductivity and breakdown voltage resistance according to claim 2, characterized in that: The high temperature curing described in step (6) is to pre-cure at 120-145°C for 2-3 hours and then cure at 150-175°C for 10-14 hours.

7. A high thermal conductivity and breakdown voltage resistant circuit board, comprising, in sequence, a composite thermal conductive insulation layer on the lower surface of a substrate layer, a substrate layer, a composite thermal conductive insulation layer on the upper surface of the substrate layer, and a conductive circuit layer; the composite thermal conductive insulation layer adopts the high thermal conductivity and breakdown voltage resistant circuit board material described in claim 1.

8. The high thermal conductivity and breakdown voltage resistant circuit board according to claim 7, characterized in that: The substrate layer is made of a mixture of one or more of copper, copper alloy, aluminum, aluminum alloy, magnesium, magnesium alloy, iron, and iron alloy; the conductive circuit layer is made of one or more materials including copper, copper alloy, aluminum, aluminum alloy, and silver; the substrate layer has a thickness of 0.1-0.5 mm, the composite thermal conductive insulation layer has a thickness of 10-35 μm, and the conductive circuit layer has a thickness of 15-35 μm.

9. The method for preparing a circuit board with high thermal conductivity and breakdown voltage resistance as claimed in claim 7, characterized in that: The method comprises the steps of preparing a high thermal conductivity and breakdown voltage resistant circuit board material on a substrate layer, and also comprises the steps of depositing a conductive circuit layer on the composite thermal conductive insulating layer by a PVD coating process using a target material.

Citation Information

Patent Citations

  • Resin composition and substance prepared from same

    CN109233543A

  • Magnetic graphene-based aerogel material with ordered structure and preparation method thereof

    CN109320286A

  • Thermal interface materials with alligned fillers

    US20160326419A1